World education encyclopedia a survey of educational systems worldwide - Marlow-Ferguson, Rebecca (Gale virtual reference library, 2002)
This 3-volume country-by-country survey of educational systems provides detailed essays on the histories, legal foundations, and primary and secondary educational systems of 233 countries. This updated and expanded edition gives users up-to-date coverage of reorganized educational systems and high-interest topics such as technological advances.